Prevalence of multiresistant gram-negative organisms in a tertiary hospital in Mwanza, Tanzania - Chakraborty Trinad; Mirambo Mariam; Kamugisha Erasmus; Mshana Stephen E; Lyamuya Eligius F (BMC Research Notes, 2009)
Abstract Background Antimicrobial resistance is fast becoming a global concern with rapid increases in multidrug-resistant Gram negative organisms. The prevalence of extended spectrum beta-lactamase (ESBL)-producing clinical isolates increases the burden on implementing infectious disease management in low socio-economic regions. As incidence can vary widely between regions, this study was done to determine resistance patterns of Gram-negative organisms at Bugando Medical Center, a tertiary hospital in Mwanza, Tanzania. Methods A total of 800 clinical samples (urine, wound swab, pus, blood, aspirate, sputum etc) were processed over a period of 6 months. Gram-negative bacteria were identified using conventional in-house biochemical tests and susceptibility to common antibiotics done using disc diffusion methods. The disc approximation method was used to identify ESBL producers. Results A total of 377 Gram-negative bacteria (GNB) recovered from 377 clinical specimens were analyzed of which 76.9% were Enterobacteriaceae. Among all GNB, 110/377 (29.2%) were found to be ESBL producers. Species specific ESBLs rate among Klebsiella pneumoniae, Escherichia coli, Acinetobacter spp, Proteus spp and other enterobacteria were 63.7%, 24.4%, 17.7%, 6.4% and 27.9% respectively. A statistically significant higher number of inpatients 100/283 (35.3%) compared to 10/94 (10.6%) of outpatients had ESBL-producing organisms (p = 0.000023). Rates of resistances to gentamicin, tetracycline, sulphamethaxazole/trimethoprim and ciprofloxacin were significantly higher among ESBLs isolates than non-ESBL isolates (p = 0.000001). Conclusion ESBL producing organisms are common at BMC (Bugando Medical Center) and pose a challenge to antibiotic therapy. Successful implementation of a routine detection of ESBL production is essential in designing appropriate antibiotic prescribing policies and infection control intervention programmes.